Book Review Understanding Power: The Indispensable Chomsky: Edited by Peter R Mitchell and John Schoeffel Vintage Books London (2003, 416 pages) - Barnes, John Arthur (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
Noam Chomsky is accepted as an eminent social critic who over the past fifty years has brought to public attention the many falsehoods perpetrated by governments and vested interests on its peoples. Chomsky has achieved this through publishing books and journal articles and engaging in lectures at MIT where he serves as full time faculty and by conducting extensive national and international tours. The editors of the volume Peter R Mitchell and John Schoeffel are public defenders in New York City. The book under review will prove to be a useful adjunct to both lecturers and students seeking to more clearly understand how the public discourse is manipulated by vested interests in governments and the public sphere.